2006
DOI: 10.1136/bjsm.2006.027557
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system stimulants and sport practice

Abstract: Doping with CNS stimulants is a real public health problem and all sports authorities should participate in its prevention. Dissemination of information is essential to prevent doping in sport and to provide alternatives. Adequate training and education in this domain should be introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 22 publications
0
61
0
2
Order By: Relevance
“…dopamine, epinephrine, serotonin), which results in a reduced sensation of fatigue, increased motor activity, and increased alertness (Avois et al, 2006). These effects make the use of stimulants attractive to college students and studies have shown that college students often engage in the misuse of prescription stimulants (MPS) at higher rates than other peers their age (Johnston, O'Malley, Bachman, Schulenberg, & Miech, 2014;McCabe, West, Teter, & Boyd, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…dopamine, epinephrine, serotonin), which results in a reduced sensation of fatigue, increased motor activity, and increased alertness (Avois et al, 2006). These effects make the use of stimulants attractive to college students and studies have shown that college students often engage in the misuse of prescription stimulants (MPS) at higher rates than other peers their age (Johnston, O'Malley, Bachman, Schulenberg, & Miech, 2014;McCabe, West, Teter, & Boyd, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These effects make the use of stimulants attractive to college students and studies have shown that college students often engage in the misuse of prescription stimulants (MPS) at higher rates than other peers their age (Johnston, O'Malley, Bachman, Schulenberg, & Miech, 2014;McCabe, West, Teter, & Boyd, 2014). MPS is problematic because it can lead to unintended consequences such as cardiac events, dehydration, insomnia, substance dependence, and death (Avois et al, 2006;Deventer, Roels, Delbeke, & Van Eenoo, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moderate doses of caffeine can lead to an increase in both physical and mental task performance [4][5][6][7][8][9][10], making caffeine an ideal compound for combating both fatigue and sub-optimal arousal. Caffeine's effect is likely attributable to its function as a mild central nervous system (CNS) stimulant [11], whereby it competitively binds to adenosine receptors, leading to a suppression of its inhibitory effect on CNS activity [12]. Accordingly, caffeine is the main physiologically active ingredient in many commercially available energy supplements [13].…”
Section: Introductionmentioning
confidence: 99%
“…109 Cocaine binds differentially to the dopamine, serotonin, and norepinephrine transport proteins, and directly inhibits the re-uptake of these neurotransmitters into pre-synaptic neurons, resulting in euphoria, pleasure and addiction. 110,111 119,120 EMIT, 112 fluorescence polarization immunoassays (FPIA) 121 and radioimmunoassays (RIA) 113 for the quantitative and qualitative detection of cocaine and its major metabolites in biofluids. Most early immunoassays used ELISA , but these tests are timeconsuming and expensive.…”
Section: Cocaine Abusementioning
confidence: 99%
“…109 Cocaine abuse can lead to several health complications such as psychosis, anxiety, paranoia, heart attacks, seizures, abdominal pain, nausea, or even death in some instances. 110 There have been reports of intracerebral hemorrhage causing bulges in the walls of cerebral blood vessels that can occur due to long-term cocaine use. 111 Therefore it is important to detect and apprehend cocaine users from bringing harm to them and people around them.…”
Section: Introductionmentioning
confidence: 99%